Floating housing; enabling self sufficient and shared communities for a sustainable future - Wang, Zhaoheng (My University, 2025)
Under the influence of global climate change, rising sea levels and increasing flood risks present unprecedented challenges to cities worldwide. These environmental changes highlight the urgent need for cities to enhance their resilience. Floating housing, as a solution providing an innovative approach to adapting to water-based environments and offers a sustainable alternative to traditional urban living, has gained global attention. However, Sweden has been relatively slow in developing this field due to reasons including regulatory barriers and limited public awareness and has yet to establish mature floating community practices. This study focuses on the Frihamnen area in Gothenburg, which has been undergoing the most significant transformation since its establishment in the 1920s. As part of the Älvstaden (River City) revitalization project, which aims to revitalize the city’s waterfront and improve its sustainability. The need to reshape and reactivate the underutilized old harbor basin presents an opportunity to rethink the potential of floating housing in this context.This research proposes the creation of a floating community within the Norra Frihamnen harbor basin to address the demand for sustainable urban housing solutions. The thesis examines the concepts of sharing communities and self-sufficiency strategies, explores how the spatial design of floating community can offer more soft values, enhance interaction among residents, improve living experiences, and contribute to a more inclusive, sustainable, and resilient form of water-based living. The thesis ultimately presents a co-living floating community proposal in the Norra Frihamnen harbor basin. Through continuous iterative optimization and refinement, this design not only offers a new perspective on the Frihamnen revitalization but also explores how floating communities can serve as a catalyst for the symbiotic development of Gothenburg and its surrounding waters. Furthermore, the thesis emphasizes the importance of raising awareness and stimulating public discussions regarding floating housing in Sweden, aiming to increase understanding and acceptance of this housing type.
Keywords: Floating housing, Shared community, Co living design, Self-sufficiency, Harbor revitalization